2020
DOI: 10.1002/macp.202000197
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Containing Thermoset Nanocomposites via Free Radical Photocrosslinking Polymerization

Abstract: Naturally occurring halloysite nanotubes (HNTs) are first functionalized by 3‐(trimethoxysilyl) propyl methacrylate and then used as nanofillers in a mixture of difunctional methacrylates (triethylene glycol dimethacrylate and bisphenol A glycerolate dimethacrylate). Upon free radical photocrosslinking of this mixture enables the in situ preparation of HNT/thermoset nanocomposites. The covalent bonding of HNT in the thermoset matrix is proven by following characteristic bands of the mixture using Fourier trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…These mechanical properties were different from those obtained in the recently published study by our team in which the HNT was modified by 3-(trimethoxysilyl) propyl methacrylate (silane agent) and the same multifunctional methacrylate monomers were used as Bis-GMA and TEGDMA. [16] This indicated that the type of silane agents directly affected the interaction mechanisms between HNT nanofiller and polymer matrices. Similar results were also reported by Xie et al [19] and Abdelmouleh et al [20] on the effects of silane coupling agent on the mechanical and outdoor performance of the natural fiber/composites.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…These mechanical properties were different from those obtained in the recently published study by our team in which the HNT was modified by 3-(trimethoxysilyl) propyl methacrylate (silane agent) and the same multifunctional methacrylate monomers were used as Bis-GMA and TEGDMA. [16] This indicated that the type of silane agents directly affected the interaction mechanisms between HNT nanofiller and polymer matrices. Similar results were also reported by Xie et al [19] and Abdelmouleh et al [20] on the effects of silane coupling agent on the mechanical and outdoor performance of the natural fiber/composites.…”
Section: Resultsmentioning
confidence: 97%
“…Due to the promising features of HNT such as large surface area and high-aspect ratio, it has been used to provide strong interfacial interactions and homogeneous dispersion in the polymer matrix. [16,18] In this work, exterior/interior hydroxyl groups of HNTs were functionalized with VTES as silylation agent to form vinyl-functional halloysite nanotubes (HNT-Vinyl). Chemical structure of obtained HNT-Vinyl was verified by both FT-IR spectroscopy and thermogravimetric analysis (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GİRİŞ HNT (1:1 katmanlı Al2Si2O5(OH)4.nH2O), geniş en boy oranı, doğal kullanılabilirliği, iyi biyouyumluluğu ve yüksek mekanik mukavemet özelliklerini içeren tek boyutlu yeni nesil doğal bir nanodolgudur [1]. Ayrıca HNT/polimer nanokompozitleri düşük maliyetle ve yüksek mekanik, termal ve biyolojik özelliklere sahip olarak hazırlanabilmektedir [2]. HNT aynı zamanda aktif maddelerin kontrollü salım uygulamalarında kullanım potansiyeline sahiptir.…”
unclassified